2017
DOI: 10.1523/eneuro.0378-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Boosting of Thalamic D2 Dopaminergic Transmission: A Potential Strategy for Drug-Seeking Attenuation

Abstract: This commentary focuses on novel findings by Clark et al. (2017) published in eNeuro, which show that dopamine D2 receptors (D2Rs) in the paraventricular nucleus of the thalamus (PVT) are involved in cocaine sensitization. We extend the discussion on how their findings contribute to our understanding of the role of the PVT in drug seeking by providing new insight on the role of the PVT in the regulation of food-seeking and fear responses. We also consider the significance of the neuroanatomical findings report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Indeed, the posterior PVT has recently been referred to as both a potential ''stressmemory'' center of the brain (Bhatnagar and Dallman, 1998;Bhatnagar et al, 2000;Fenoglio et al, 2006;Heydendael et al, 2011) and the whole nucleus as the ''traffic light of motivated behaviors'' (McGinty and Otis, 2020). The past decade has seen multiple review articles and commentaries describing the heterogeneity of PVT anatomy, diverse neurochemistry, and functions (James and Dayas, 2013;Do-Monte and Kirouac, 2017;Millan et al, 2017;Barson et al, 2020), including a potential role in long-term fear memory (Padilla-Coreano et al, 2012;Penzo et al, 2015;Do-Monte et al, 2016), salience, conflict resolution (Choi and McNally, 2017;Choi et al, 2019), motivated memory, and associated behaviors (Kirouac, 2015;Millan et al, 2017;Zhu et al, 2018;Zhou and Zhu, 2019;Lucantonio et al, 2020). However, given its small size [e.g., ∼7 mm 3 for left paraventricular nucleus (Krauth et al, 2010;Jo et al, 2019)], there is a dearth in our understanding of PVT function in the human brain.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the posterior PVT has recently been referred to as both a potential ''stressmemory'' center of the brain (Bhatnagar and Dallman, 1998;Bhatnagar et al, 2000;Fenoglio et al, 2006;Heydendael et al, 2011) and the whole nucleus as the ''traffic light of motivated behaviors'' (McGinty and Otis, 2020). The past decade has seen multiple review articles and commentaries describing the heterogeneity of PVT anatomy, diverse neurochemistry, and functions (James and Dayas, 2013;Do-Monte and Kirouac, 2017;Millan et al, 2017;Barson et al, 2020), including a potential role in long-term fear memory (Padilla-Coreano et al, 2012;Penzo et al, 2015;Do-Monte et al, 2016), salience, conflict resolution (Choi and McNally, 2017;Choi et al, 2019), motivated memory, and associated behaviors (Kirouac, 2015;Millan et al, 2017;Zhu et al, 2018;Zhou and Zhu, 2019;Lucantonio et al, 2020). However, given its small size [e.g., ∼7 mm 3 for left paraventricular nucleus (Krauth et al, 2010;Jo et al, 2019)], there is a dearth in our understanding of PVT function in the human brain.…”
Section: Introductionmentioning
confidence: 99%
“…For these studies, the effects of PrL-PVT manipulation were examined early in Pavlovian training, when Pavlovian cues are known to evoke a DA response in the NAc to a different degree in STs and GTs 28,56 . Although we expected to observe more robust behavioral effects during this period, we found that stimulation of the PrL-PVT pathway early in Pavlovian training did not affect the behavior of STs, nor did it significantly affect extracellular It has become increasingly apparent in recent years that the PVT and its associated circuitry play an important role in motivated behaviors, including those related to addiction and anxiety-related disorders 16,33,[57][58][59][60][61][62][63][64][65][66][67][68] . Here, we honed in on the PrL-PVT pathway and exploited an animal model of individual differences in cue-reward learning to demonstrate that this circuit acts as a top-down control mechanism to suppress the attribution of incentive value to a food-paired cue.…”
Section: Discussionmentioning
confidence: 72%
“…It has become increasingly apparent in recent years that the PVT and its associated circuitry play an important role in motivated behaviors, including those related to addiction and anxiety-related disorders (Coffey et al, 2010; Do-Monte et al, 2015; Matzeu et al, 2015; Zhu et al, 2016; Choi and McNally, 2017; Do-Monte and Kirouac, 2017b; Do-Monte et al, 2017a; Matzeu et al, 2017; Millan et al, 2017; Otis et al, 2017; Beas et al, 2018; Giannotti et al, 2018; Zhu et al, 2018; Choi et al, 2019). Here, we honed in on the PrL-PVT pathway and exploited an animal model of individual differences in cue-reward learning to demonstrate that this circuit acts as a top-down control mechanism to suppress the attribution of incentive value to a food-paired cue.…”
Section: Discussionmentioning
confidence: 99%